The Impact of Financial Stress on Academic Performance in Tertiary Education: Empirical Evidence from Comilla University - Sharna Mazumder (Ekonomikalia Journal of Economics, 2026)
University students commonly struggle with financial stress, which has consequences for both their general well-being and academic achievement. This paper aims to explore the impact of financial stress on academic performance. A quantitative study was conducted at Comilla University, a tertiary institution in Bangladesh. The study included 152 randomly selected students from different departments who are currently enrolled in undergraduate and postgraduate programs. Primary data were used in both descriptive and inferential analyses. Descriptive analysis, including students’ perceptions and opinions regarding financing expenses, unexpected expenses, family financial obligations, tuition fees, living expenses, the cost of books and study materials, and financial support to family, showed that these factors led to financial stress and affected students’ academic performance. From the descriptive analysis, the study found that higher living expenses mostly affected students’ academic performance. The inferential analyses, including t-tests, hypothesis tests, and regression analysis, found different factors that significantly affected students’ academic performance. In the gender analysis using t-tests, it was found that female students reported slightly higher stress levels but performed better academically than males. From the correlation analysis, we found a positive relationship. Family income and class attendance were positively correlated with students’ academic performance, while working hours negatively impacted CGPA. The regression analysis revealed class attendance and family income as statistically positive factors that positively affected students’ academic performance. Working hours negatively affected academic performance and were statistically significant. Based on the results, the study recommends that, in order to mitigate the adverse impacts of financial stress on academic performance, Comilla University, as well as the government, should strengthen financial aid programs, create on-campus employment opportunities, and provide counseling on time management.